2004
DOI: 10.1152/ajpcell.00201.2003
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR/p70 S6K1 pathway regulates vascular smooth muscle cell differentiation

Abstract: Vascular smooth muscle cells (VSMC) in mature, normal blood vessels exhibit a differentiated, quiescent, contractile morphology, but injury induces a phenotypic modulation toward a proliferative, dedifferentiated, migratory phenotype with upregulated extracellular matrix protein synthesis (synthetic phenotype), which contributes to intimal hyperplasia. The mTOR (the mammalian target of rapamycin) pathway inhibitor rapamycin inhibits intimal hyperplasia in animal models and in human clinical trials. We report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 45 publications
9
178
0
Order By: Relevance
“…Intimal hyperplasia may be induced upon vessel injury, causing the vascular smooth muscle cells to change from a quiescent, differentiated, contractile phenotype to a more proliferative, dedifferentiated, and migratory phenotype (reviewed in Owens, 1995). Rapamycin inhibits the increased proliferation and migration of vascular smooth muscle cells that occurs after injury (Poon et al, 1996;Gallo et al, 1999;Roque et al, 2000) and also induces their differentiation back toward a more mature phenotype (Martin et al, 2003). The injury-induced expression of several cell cycle regulatory proteins is inhibited by the in vivo administration of rapamycin to rats, suggesting a mechanism for the antirestenotic effect of rapamycin on proliferation (Braun-Dullaeus et al, 2001).…”
Section: A Role For Tor In Other Human Disease Statesmentioning
confidence: 99%
“…Intimal hyperplasia may be induced upon vessel injury, causing the vascular smooth muscle cells to change from a quiescent, differentiated, contractile phenotype to a more proliferative, dedifferentiated, and migratory phenotype (reviewed in Owens, 1995). Rapamycin inhibits the increased proliferation and migration of vascular smooth muscle cells that occurs after injury (Poon et al, 1996;Gallo et al, 1999;Roque et al, 2000) and also induces their differentiation back toward a more mature phenotype (Martin et al, 2003). The injury-induced expression of several cell cycle regulatory proteins is inhibited by the in vivo administration of rapamycin to rats, suggesting a mechanism for the antirestenotic effect of rapamycin on proliferation (Braun-Dullaeus et al, 2001).…”
Section: A Role For Tor In Other Human Disease Statesmentioning
confidence: 99%
“…Recombinant adenovirus encoding HA tagged the constitutively active and rapamycin-resistant S6K1 (Ad-S6K1-ca) was generated and amplified using the ViraPowert Adenoviral Expression System (Invitrogen, Carsbad, CA, USA), following the manufacturer's instruction. The recombinant adenovirus (Ad-S6K1-wt) encoding HA-tagged wild-type S6K1 was prepared, as described previously (Martin et al, 2004). These viruses were co-expressing GFP, and titrated by visualization of GFP expression in HEK 293 cells 24 h post-infection under a fluorescence microscope (Nikon TE300).…”
Section: Recombinant Adenoviral Constructs and Infection Of Cellsmentioning
confidence: 99%
“…However, recent concerns about the risk of late thrombosis with these stents, likely as a result of impaired re-endothelialization (4), reveals the need for a better understanding of the mechanisms of action of rapamycin on VSMCs to develop VSMC-specific therapies. Although it is known that rapamycin inhibits VSMC migration (5) and proliferation (6) in vitro and intimal hyperplasia in vivo, we have recently demonstrated that rapamycin also induces differentiation in cultures of synthetic phenotype VSMCs (7). This occurs as a coordinated induction of cyclin-dependent kinase inhibitor (p21 cip and p27 kip ) and contractile protein expression, which begins as early as 2 h following rapamycin treatment.…”
mentioning
confidence: 90%